Facile electrochemical preparation of a composite film of ruthenium dioxide and carboxylated graphene for a high performance supercapacitor. Issue 40 (6th April 2016) - Meng, Yue; Wang, Linping; Xiao, Hongbo; Ma, Yixuan; Chao, Long; Xie, Qingji
Abstract : A high performance supercapacitor based on a composite of ruthenium dioxide and carboxylated graphene is constructed by composite electrodeposition and electrooxidation. Abstract : Ruthenium and carboxylated graphene (CG) were co-electrodeposited at −0.25 V vs. SCE on a quartz crystal microbalance (QCM) Au electrode in a stirred aqueous dispersion containing 0.6 mM RuCl3, 1 mg mL −1 CG and 0.1 M H2 SO4 . The Ru–CG composite was electrooxidized by cyclic voltammetry in 0.5 M aqueous H2 SO4 to yield a RuO2 –CG/QCM electrode for supercapacitor research. In situ QCM technique and ex situ scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD) spectroscopy, and Raman spectroscopy were used for process monitoring and/or film characterizations. The RuO2 –CG/QCM electrode exhibited an apparent specific capacitance of 756 F g −1, an energy density of 101 W h kg −1 at a power density of 2.5 kW kg −1, and high stability. The specific capacitance is higher than those of similarly prepared RuO2 /QCM, RuO2 –multiwalled carbon nanotubes (MWCNTs)/QCM, RuO2 –graphene oxide/QCM electrodes and a cast-coated CG/QCM electrode, as well as many reported RuO2 -based electrodes. The present method for the preparation of the RuO2 –CG composite film only needs two simple electrochemical processes (solution-stirred composite electrodeposition and then a solution-quiescent anodic treatment), which is promising for the facile preparation of other similar nanocomposite films for wider applications.